2010
DOI: 10.1080/00480169.2010.65265
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of suspected congenital luxation of the radial head in three dogs

Abstract: Congenital luxation of the radial head is an uncommon condition that has conflicting reports in the literature regarding its cause, heritability, breed predisposition, treatment and prognosis. The three cases here occurred in young dogs of English Bull Terrier, Jack Russell Terrier, and Staffordshire Bull Terrier breeds. Surgical reduction and stabilisation provided successful outcomes, in all cases. Only six cases of congenital luxation of the radial head managed surgically have previously been reported in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 12 publications
2
28
0
Order By: Relevance
“…Developmental canine radial head luxation is a rare condition that lacks a well-defined treatment method with a consistently successful outcome (14). To date, there are only 16 documented cases of the surgical management of congenital or developmental canine radial head luxation (14,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Developmental canine radial head luxation is a rare condition that lacks a well-defined treatment method with a consistently successful outcome (14). To date, there are only 16 documented cases of the surgical management of congenital or developmental canine radial head luxation (14,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Developmental canine radial head luxation is a rare condition that lacks a well-defined treatment method with a consistently successful outcome (14). To date, there are only 16 documented cases of the surgical management of congenital or developmental canine radial head luxation (14,(17)(18)(19). Although these reports share a surgical N. Fitzpatrick et al: Management of radial head luxation with external skeletal traction Figure 6 Orthogonal radiographs of the right elbow taken four months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Type 1 congenital elbow luxation (CEL), where the radial head is luxated caudolaterally without disruption of the humeroulnar joint (Kene et al 1982, Griffon 2011) is most commonly reported in large breed dogs (Grondalen 1973, Campbell 1979, Kene et al 1982, Milton & Montgomery 1987, Spardari & Romagnoli 2001, Temwichitr et al 2010 with only two reports in small breed dogs including a dachshund and a Jack Russell terrier (Fafard 2006, Clark & Jerram 2010. Affected puppies are reported to have a mild forelimb lameness, which is first noticed at around 3 to 4 months of age and pain on manipulation of the elbow with a reduced range of motion in flexion and extension.…”
Section: Introductionmentioning
confidence: 99%